IMPLEMENTASI RENCANA KEGIATAN DAN ANGGARAN SEKOLAH BERBASIS FUNGSI MANAJEMEN POAC DALAM MENDUKUNG EFEKTIVITAS PROGRAM PENDIDIKAN DI SMK LABSCHOOL 1 SURABAYA - Oryza Hafshah Syafira; Melani Khairunnisa; Wahyu Rizky Aprilian; Adinda Aurilia Putri; Nana Pesona Islami; Chelsea Tri Hapsari; Ima Widiyanah (STKIP Subang, 2026)
The School Activity and Budget Plan (RKAS) constitutes a fundamental instrument of school financial management, particularly for private vocational schools that operate under three distinct funding streams: School Operational Assistance (BOS) from the central government, Provincial Education Support Funds (BPOPP) from the provincial government, and community-sourced funds (SPP) administered by the school foundation. Each stream carries distinct regulatory obligations and cannot be used interchangeably, creating a level of financial governance complexity that significantly exceeds that of public general secondary schools. This study aims to analyze RKAS implementation through the POAC management framework (Planning, Organizing, Actuating, Controlling) at SMK Labschool 1 Surabaya and its relationship with educational program effectiveness. A qualitative single-case study design was employed; data were collected through in-depth interviews with the Principal and School Treasurer, structured observation, and documentation analysis conducted on April 21, 2026. Findings reveal that: (1) planning was executed participatively based on the eight National Education Standards with a fully non-cash procurement mechanism through SIPLA-ARKAS integration; (2) organizing applied a dual-control mechanism between the Principal and Treasurer alongside a clear separation of SPP management through the foundation; (3) actuating demonstrated consistent program realization supported by monthly evaluation cycles; and (4) controlling operated through layered internal evaluations, quarterly provincial supervisory visits, and real-time digital monitoring by the State Audit Board. Synergistic implementation across all POAC functions demonstrably supported educational program effectiveness. A primary recommendation is the pre-planned allocation of a contingency budget reserve to reduce reliance on departmental student funds for mid-year shortfalls.